Autoeficacia y vivencias académicas en estudiantes universitarios (2017)
The aim of this study was to analyze the relationship between the dimensions of the self-efficacy construct in academic behaviors and academic experiences with undergraduate students. 405 students of Psychology, Engineering and Pedagogy from various Chilean universities participated. The sampling was non probabilistic. The Self-efficacy Scale in Academic Behaviors and the Academic Experiences Questionnaire were applied. Analysis of correlations between variables and canonical correlations were performed. Direct relationships were found between the dimensions of self-efficacy in academic behaviors and academic experiences, except in academic self-efficacy and personal difficulties, where an inverse relationship was found. The findings were consistent with previous studies which refer to correlations between variables. There were three canonical dimensions describing students according to their university studies: real self-efficacy vs. academic experience based on study strategy; communication style and excellence vs. personal and interpersonal style, and general attention vs. assessment of the studies and the institution.